1999
DOI: 10.1002/(sici)1099-1352(199911/12)12:6<390::aid-jmr482>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the 1998 optical biosensor literature

Abstract: The utilization of optical biosensors to study molecular interactions continues to expand. In 1998, 384 articles relating to the use of commercial biosensors were published in 130 different journals. While significant strides in new applications and methodology were made, a majority of the biosensor literature is of rather poor quality. Basic information about experimental conditions is often not presented and many publications fail to display the experimental data, bringing into question the credibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 373 publications
0
58
0
2
Order By: Relevance
“…Densities of each fraction are indicated (in g͞ml), and a CCR5 standard was run in the far right lane to control for expression. (22). Because viral particles are likely to be negatively charged and surface plasmon resonance decays exponentially as a function of distance from the biosensor surface, we used a carboxymethylated surface that lacks a dextran matrix (Biacore C1 chip).…”
Section: Resultsmentioning
confidence: 99%
“…Densities of each fraction are indicated (in g͞ml), and a CCR5 standard was run in the far right lane to control for expression. (22). Because viral particles are likely to be negatively charged and surface plasmon resonance decays exponentially as a function of distance from the biosensor surface, we used a carboxymethylated surface that lacks a dextran matrix (Biacore C1 chip).…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 RT uses a tyrosine residue at position 115 (Tyr-115) as steric gate, and mutations of this residue have been shown to promote greater rNTP incorporation (10). Despite this discriminatory mechanism, it has been shown that cellular DNA polymerases do incorporate rNTPs during DNA synthesis (7,11,12). We have previously demonstrated that HIV-1 RT frequently incorporates rNTPs during DNA synthesis under macrophage dNTP/ rNTP conditions at ratio of 1 rNTP every 146 bases (4,13).…”
mentioning
confidence: 99%
“…3), reproducibly achieving immobilization levels of 70-200 response units relative to the ethanolamine-capped control surface. This low immobilization level was targeted to allow kinetic measurements of the system (Karlsson et al, 1991;Myszka, 1999). CYP2C9i was then exposed to soluble CYP2C9, CYP2D6, or CYP3A4 to analytically determine equilibrium dissociation constants for each dimer pair.…”
Section: Resultsmentioning
confidence: 99%